Physical and mechanical properties of Eucalyptus saligna wood for timber structures - Nogueira, Marta Cristina de Jesus Albuquerque (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2019)
Due to its great availability in planted forests in Brazil,Eucalyptus saligna appears as a good species to be exploited,  in order to assist in the consumption of wood for construction purposes. The aim of this research was to determine the physical and mechanical properties of Eucalyptus saligna wood species for its use in civil construction. The evaluation was based on 16 physical and mechanical properties obtained according to NBR 7190 (1997) standard. Two values of moisture content were considered: 30% (above the fiber saturation point) and 12% (equilibrium moisture content) according to NBR 7190 (1997). All obtained results obtained were statistically analyzed according to the t-test at the 5% level of significance. In addition, the characteristic strength properties were also determined, for batch classification in the strength classes recommended by the Brazilian standard. Eucalyptus saligna had an apparent density of 0.58 g/cm³ and a basic density of 0.73 g/cm³. The mechanical properties, presented fc0 and fc0,k equal to 46.80 and 32 MPa, respectively. The results indicated that Eucalyptus saligna wood can be used in the construction of timber structures as structural member.